2016
DOI: 10.1111/bph.13574
|View full text |Cite
|
Sign up to set email alerts
|

Robust anti‐nociceptive effects of monoacylglycerol lipase inhibition in a model of osteoarthritis pain

Abstract: BACKGROUND AND PURPOSEChronic pain is often a symptom of knee osteoarthritis (OA) for which current analgesics are either inadequate or are associated with serious side effects. The endocannabinoid system may offer alternative targets for pain relief. We evaluated the effects of a potent and selective monoacylglycerol (MAG) lipase inhibitor (MJN110) on OA pain behaviour, spinal mechanisms of action and joint histopathology in the rat. EXPERIMENTAL APPROACHIntra-articular injection of monosodium iodoacetate (MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 44 publications
(56 reference statements)
4
28
0
Order By: Relevance
“…The anti-allodynic effects of MJN110 were mediated by a CB 2 receptor mechanism of action, while CB 1 receptors did not play a necessary role in this effect. However, weight bearing was only partially blocked by the CB 2 receptor antagonist, SR144528, but fully blocked by rimonabant, indicating a difference in receptor mechanism (Burston et al, 2016).…”
Section: Endocannabinoids and Painmentioning
confidence: 94%
“…The anti-allodynic effects of MJN110 were mediated by a CB 2 receptor mechanism of action, while CB 1 receptors did not play a necessary role in this effect. However, weight bearing was only partially blocked by the CB 2 receptor antagonist, SR144528, but fully blocked by rimonabant, indicating a difference in receptor mechanism (Burston et al, 2016).…”
Section: Endocannabinoids and Painmentioning
confidence: 94%
“…The antinociceptive effects observed at the ED 50 were associated with ABD-1970 concentrations less than 10 nM in the brain and blood, 40% inhibition of brain MGLL activity, and 3-fold elevations in brain 2-AG concentrations. Multiple previous studies have demonstrated sustained antinociceptive, antiallodynic, and antihyperalgesic effects after repeated administration of MGLL inhibitors at low doses that partially inhibit MGLL in the brain (Busquets-Garcia et al, 2011;Kinsey et al, 2013;Burston et al, 2016;Curry et al, 2018), whereas tolerance to these effects has been observed after prolonged, complete MGLL inhibition or genetic ablation (Chanda et al, 2010;Schlosburg et al, 2010;Ignatowska-Jankowska et al, 2014). The functional tolerance observed with complete MGLL inactivation and maximal elevation of brain 2-AG concentrations is associated with downregulation and/or desensitization of brain CB1 receptors (Chanda et al, 2010;Schlosburg et al, 2010;Navia-Paldanius et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…MJN110, a prototypic MAGL inhibitor, has shown to be effective at alleviating neuropathic pain in animal models (Burston et al, 2016;Wilkerson et al, 2016). Cancer-induced bone pain (CIBP) displays characteristics of neuropathic and inflammatory pain (Lozano-Ondoua et al, 2013b;Slosky et al, 2016); thus targeting pain of inflammatory and neuropathic origin is rational.…”
Section: Discussionmentioning
confidence: 99%